Health information seeking on the Internet: The role of involvement in searching for and assessing online health information. Issue 4 (1st October 2016) - Park, Sun-Young; Go, Eun
ABSTRACT: This study focuses on how young people with differing levels of involvement seek and evaluate information about the human papillomavirus online. The results, which are drawn from an experiment and a self-administered survey, suggest that compared to people with a low level of involvement, people with a high level of involvement engage in more information search activity. The results also indicate that those with a high level of involvement in a given subject place a higher value on a website's message features than on its structural features. Implications, limitations, and suggestions for future research are discussed.